2020
DOI: 10.1016/j.arthro.2019.11.094
|View full text |Cite
|
Sign up to set email alerts
|

Editorial Commentary: Revision of Failed Double-Bundle Anterior Cruciate Ligament Reconstruction

Abstract: Double-bundle (DB) reconstruction of the anterior cruciate ligament was favored for several years. However, recent studies increasingly show that this technique does not provide a clear advantage over the less-invasive singlebundle technique. Unfortunately, the graft fails relatively often after ACL reconstruction. Postoperative communication of the bone tunnels through bone tunnel widening is possible. Since 2 drill channels are created in the DB technique, femoral as well as tibial, it is assumed that this t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The classi cation aimed to describe the position of the femoral tunnel with surrounding bony landmarks for the selection of different operation method for ACL revision. Zauleck et al found LIR was a reliable bony landmark helping the surgeon analyze and judge the anterior and posterior location of the tunnel [23]. However, it was di cult to identify the speci c location of LIR on CT two-dimensional imaging due to the in uence of the OT [17,18], and the LIR was almost entirely dependent on relative anatomical knowledge and clinical experience in the Robert femoral tunnel classi cation, which substantially decreased the objectivity of the results [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The classi cation aimed to describe the position of the femoral tunnel with surrounding bony landmarks for the selection of different operation method for ACL revision. Zauleck et al found LIR was a reliable bony landmark helping the surgeon analyze and judge the anterior and posterior location of the tunnel [23]. However, it was di cult to identify the speci c location of LIR on CT two-dimensional imaging due to the in uence of the OT [17,18], and the LIR was almost entirely dependent on relative anatomical knowledge and clinical experience in the Robert femoral tunnel classi cation, which substantially decreased the objectivity of the results [12].…”
Section: Discussionmentioning
confidence: 99%
“…For example, the femoral double tunnel was di cult to make a selection of revision strategy, and even if the position of the double tunnel was correct, the expanded double tunnel could still probably run through a huge tunnel (Fig. 4f) [23]. Therefore, only the second-phase revision or OTT reconstruction could be chosen to deal the di cult problem.…”
Section: Discussionmentioning
confidence: 99%
“…R‐ACLRs tend to result in worse outcomes than that of primary operations [5, 6]. As such, technical aspects of r‐ACLR have been studied extensively in the adult literature over the past several years, including optimal graft selection, tunnelling and fixation strategies, and staging [7–9]. Up to 90% of paediatric and adolescent patients return to sport after index procedures [10], therefore, it is critical for orthopaedic surgeons to have a comprehensive understanding of the most commonly used operative techniques in both primary and revision ACLR for the skeletally immature population.…”
Section: Introductionmentioning
confidence: 99%